Analysing Regional Differences of Agricultural Land Use and Land‐Use Change (2005‐2010) in Hesse, Germany. - Lüker-Jans, Nicola (My University, 2017)
Die Landwirtschaft produziert nicht nur landwirtschaftliche Güter, sondern sie schafft auch Landschaft. Obwohl natürliche Faktoren von entscheidendem Einfluss sind, ist es die Landnutzung und insbesondere die Landwirtschaft, die eine Vielfalt von heterogenen Landschaften hervorgebracht hat. Vor dem Hintergrund der ab Mitte des 20. Jahrhunderts vorherrschenden modernen intensiven Landwirtschaft mit einem hohen Einsatz von Düngern, Pestiziden und Bewässerung sowie der Nutzung von Flächen für Bioenergiepflanzen, wurden in der Arbeit eine regional differenzierte Analyse der Landnutzung sowie deren Änderungen erstellt. Basierend auf zwei unterschiedlichen Publikationen war es Ziel der Arbeit, (i) eine Klassifikationsmethode zu entwickeln, mit Hilfe derer räumliche und zeitliche Unterschiede im Muster der Landnutzung bestimmt werden können (Kapitel 2) und (ii) sowohl die Flächenveränderungen von Dauergrünland und Mais zu untersuchen als auch zu analysieren, ob es eine Beziehung zwischen Biogasanlagen – und zum Vergleich zwischen der Viehwirtschaft – und den Veränderungen in der Landnutzung gibt (Kapitel 3).

Agricultural land use does not only produce agricultural goods, it also creates landscapes. Primarily, agricultural land use caused an increase in biodiversity due to a variety of heterogeneous landscapes. But this positive effect turned back with the beginning of modern agricultural cultivation. Thus, intensive land use features rather negative consequences for biotic and abiotic resources. Furthermore, it is expected that the contemporaneous marginalisation causes a decrease in habitats and in biodiversity. In recent years, another trend in land use is the growing cultivation of bioenergy plants. Agricultural land use has always been dynamic and is expected to experience ongoing changes in the coming decades. Thus, a thorough understanding of past and recent land-use dynamics is essential in order to understand how agricultural land use might develop in the future, which consequently generates the basis for future management processes. Given this background, the present thesis analysed the regional differences of agricultural land use and land-use change. As described in two separate papers, this thesis aims at (i) developing a classification method to detect spatial and temporal differences of the patterns of agricultural land use (Chapter 2), and (ii) examining the area changes of permanent grassland and maize as well as analysing if there is a relationship of biogas plants and, for comparison, livestock farming to the changes in agricultural land use (Chapter 3).
Regionale Differenzierung der Landnutzung und deren Veränderungen in Hessen (2005-2010).
Keywords: Landwirtschaft; Landnutzung; Landwirtschaftliche Bodennutzung; Bioenergie; Grünland; Mais; Datenanalyse; Flächenverbrauch; Viehwirtschaft; Standortbedingung; Flächennutzung; Regionale Disparität; Subregion